KAJIAN FASILITAS PASAR CITRA NIAGA DI KABUPATEN JOMBANG - Yasqi Ilyadiana Putri; Tigor W. S. P; Farida Murti (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2023)
Citra Niaga Market is a traditional market classified as 1A located in Jomban Regency. The availability of good basic infrastructure and facilities is critical to improving the quality and sustainability of this traditional market. As part of this study, a study will be conducted on the availability and needs of basic infrastructure and facilities at the Citra Niaga market facility in Jombang district. The study was conducted using a qualitative descriptive method to describe the actual conditions of each market and was evaluated using the People's Market SNI as the compliance standard. The obtained results show that the facilities of the Citra Niaga Jombang market are not adequate and well maintained and there is a need to improve the quality of management.